The Function of Naqshabandi order by A 19th Malay Naqshabandi Scholar, Shaykh Islam Wan Sulaiman Wan Sidek (d.1354H/1935M) - Muhammad Khairi Mahyuddin (Center for Promoting Ideas, USA, 2024)
Volume: 6 No: 4